Intergalactic Triumph: American Hegemony Represented in Arrival (2016) Movie - Ramadhana, Bella Ernita (Jurnal Bahasa, Sastra, dan Studi Amerika, 2021)
This research examines a Hollywood movie entitled Arrival (2016) to see how American hegemony is represented and maintained in the movie. This is a qualitative research that is conducted under the framework of American studies. The concept of American values, Hegemony by Antonio Gramsci and Soft Power by Joseph Nye are used to answer the research questions. Semiotic film theory is employed to analyze the data in the form of dialogues and movie scenes. The results show the representation of American hegemony is seen in the characters that show American values, the U.S foreign policy, the U.S military supremacy, and the U.S economic field. Meanwhile, the maintenance of American hegemony is represented in American’s destiny to unify the world and also in hegemony through the language.